Media, propaganda and politics in 20th-century Japan - Kushner, Barak 1968-; Funabashi, Yåoichi 1944-; Asahi Shinbun "Kenshåo, Shåowa Håodåo" Shuzaihan (London Bloomsbury Academic, 2015)
This book investigates the role played by the Asahi Newspaper, one of Japan's largest daily newspapers, as a mediator of information and power during the twentieth century. Members of staff at the paper, including Funabashi Yoichi, former Editor-in-Chief and one of the most trusted public intellectuals in Japan, examine the paper's role in Japanese history, showing how news agencies assisted in the creation and maintenance of the nation's goals, dreams, and delusions. The book draws on internal documents, committee meeting notes, and interviews with the staff at the company as a means to narrate what newspaper editors chose to publish during Japan's journey through the twentieth century. As well as offering an original insight into wartime media, [this book] explores the relationship between media and society during the postwar era and into the twenty-first century. -- Back cover.
The last days of an era -- The beginning of the Showa era-economic depression -- Supreme command violated! -- The Manchurian incident -- The age of terrorism -- On the road to developing a national mythology -- The road to the Japan-US war -- The wartime greater East Asia conference -- Countdown to the war's end -- The puzzle of the August 15 edition -- The fate of 6.6 million abroad -- Newspapers under the occupation -- Layers of responsibility -- The Korean war and peace treaties -- The Bandung conference -- Restoring Japanese-Soviet relations and joining the United Nations -- The 1960 security treaty -- High-speed growth and the Tokyo Olympics -- The polluted archipelago -- Gazing at the two Koreas -- Youth revolts -- Military bases-Okinawa -- The cultural revolution and the re-opening of Sino-Japanese relations -- The Lockheed incident -- The oil shock -- Yasukuni shrine visits -- The bubble economy.
Includes bibliographical references and index.
Keywords: Asahi shinbun; Asahi shinbun -- Influence; Mass media -- Social aspects -- Japan -- History -- 20th century; Japanese newspapers -- History -- 20th century; Mass media and propaganda -- Japan -- History -- 20th century; Japan -- History -- Shåowa period, 1926-1989.; Japan -- Politics and government -- 20th century